APPARATUS FOR CULTIVATING SEA CUCUMBER HAVING HIDING ELEMENT - PARK, SONG BUM (2016)
A sea cucumber cultivating device includes: adhesive materials (10) installed in a specific part of a cultivating farm or under the sea and enabling the growth of sea cucumbers on a surface thereof; supporters (20) fixated to the adhesive materials (10) horizontally placed in layers; supporting units (30) formed in a lower side of the adhesive materials; and hiding members arranged on the bottoms of the adhesive materials and fixated to the supporting units (30) at the same time. The adhesive materials (10) are arranged to be inclined toward a direction vertical to the ground. The supporting units are arranged on the bottoms of the adhesive materials (10) in a v form. The purpose of the present invention is to provide the sea cucumber cultivating device capable of discharging the excrement of sea cucumbers existing on the supporting units using discharging modules in a simple method. 해삼 양식 장치는 바닷속 또는 축제식양식장의 일정 지역에 설치되어 해삼이 그 표면에서 생육 상태를 이루게 하는 부착기(10); 수평 방향으로 적층되는 상기 부착기(10) 상에 고정되는 지지대(20); 상기 부착기(10)의 하부에 배치되는 받침부(30); 및 상기 부착기(10) 하부에 배치되는 동시에 상기 받침부(30) 상에 고정되는 은신 부재(40);를 포함하며, 상기 부착기(10)는 지면에 수직한 방향을 기준으로 하여 경사지게 배치되며, 상기 받침부(30)는 상기 부착기(10)의 하부에 ∨ 형상으로 배치된다.